Hubungan Persepsi Orang Tua Mengenai Pendidikan Seks Terhadap Regulasi Diri Anak - Fareza, Anggun; Widayati, Sri; Agustin Ningrum, Mallevi; Adhe, Kartika Rinakit (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2024)
Sex education for children is not just about directing how to have sex. Some of them are body parts, caring for the body, maintaining behavior according to environmental norms. Parents' perceptions regarding sex education cannot be separated from the surrounding environment. The environment influences children's self-regulation. Self-regulation has a major influence on children's emotional and social development. This research uses a quantitative approach using a correlation research model. The sample in this study were parents who had children aged 5-6 years at KB-TK Khodijah. The data collection technique uses a questionnaire. The data obtained was then analyzed using the SPSS application program. The research results obtained are that there is a relationship between parents' perceptions of sex education and children's self-regulation, with a low degree of relationship and the form of the relationship, namely a positive relationship.